Psychosocial job adversity and health in Australia: analysis of data from the HILDA Survey - Liana, S; Rodgers, B; Strazdins, L; Broom, D; Olesen, S; Butterworth, P (My University, 2011)
Objective: This study examines measures of psychosocial job quality developed from the Household Income and Labour Dynamics in Australia (HILDA) Survey, and reports on associations with physical and mental health. Methods: The study used seven waves of data from the HILDA Survey with 5,548 employed respondents. Longitudinal random-intercept regression models assessed the association of time-varying and between-person measures of psychosocial job quality job adversity with physical and mental health. Results: Respondents’ specific experience of psychosocial job adversity, except marketability, was associated with increased risk of mental health problems, whereas the association between psychosocial job adversity and physical health was largely driven by differences between people. Conclusions and Implications: Moving into jobs with different psychosocial quality is associated with changes in mental health. In contrast, individuals with poor physical health show an increased propensity to work in poor-quality jobs but it seems that changes in physical health are not as strongly tied to changes in job quality. Differences in the relationship between physical and mental health and psychosocial job quality have implications for the design of employment, health and social policy. The HILDA Survey is an important resource for policy development in Australia, and the availability of valid measures of psychosocial of job quality will enhance its use to better understand this important determinant and correlate of health.
Australian and New Zealand Journal of Public Health
Keywords: Health -- Mental; Health -- Physical; Employment; Health and wellbeing; Labour market; Health; Employment; Mental; Physical; Employment and unemployment; Health and wellbeing